Pengembangan Strategi City Branding melalui Kerangka Kerja Konseptual: Menyajikan Alat Implementasi Praktikal kepada Pemerintah Kota - Ariwibowo, Rinto; Prasetyo, Galih (Jurnal Bina Praja, 2023)
City branding has gained increasing importance in recent years due to its perceived economic and political implications, necessitating the involvement of city governments and stakeholders in developing a successful cross-sectoral branding strategy. In this study, the researcher conducted a literature review and identified three critical dimensions - politics and compliance, socioeconomics, and sustainability - that must be considered when creating an implementation checklist for city regulators and executives. To address the research gap, the researcher developed a conceptual and practical framework that introduces three new terms - city branding image objects, artifacts, and infrastructure - essential in implementing city branding strategies in Indonesia. This study provides a comprehensive implementation framework checklist for city governments to ensure their branding strategy meets the three-dimensional criteria and has an appropriate implementation plan. Furthermore, the researcher expects that this article will initiate and stimulate a discussion on city branding strategies, anticipate that this study will offer an alternative perspective on city branding strategy and provide a valuable implementation tool for regulators, executives, and academics involved in city branding in Indonesia.